PENGARUH KEPERCAYAAN DAN IMAGE TERHADAP KEPUASAN NASABAH PADA BANK PEMERINTAH (STUDI KASUS PADA MAHASISWA STIE IPWIJA JAKARTA) - M. Asari; Siti Rubiah (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2017)
To win the competition in the banking industry, Bank Government should manage image bank, one of which can be done through increased customer confidence, customer confidence can create satisfaction for its customers as a form of attitude to a positive image for the bank to get a loyal customer. The purpose of this study was to determine the effect of trust on customer satisfaction. To determine the effect of image on customer satisfaction. To determine the effect of trust on customer satisfaction and image. T value for the trust (X1) at 3,089, while the value ttabel for N = 50 is equal to 2.013. So 3,089 > 2,013, then H0 is rejected and Ha is accepted, it can be stated that the trust (variable X1) does have a significant influence on customer satisfaction (Variable Y) at State Bank (Case Study on Students of Economics IPWIJA Jakarta). T value for the image (X2) at 6,244, while the value ttabel for N = 50 is at 2,013 so 6,244 > 2,013, then H0 is rejected and Ha is accepted, it can be stated that the image (variable X2) does have a significant influence on customer satisfaction (Variable Y) the State Bank (Case Study on Students of Economics IPWIJA Jakarta). Value of 49 028 Medium Fcount Ftabel (0.05) for N = 50 is equal to 2.79. So F count > F table of (0.05) or 49.028 > 2.79 with a significant level of 0.001 for 0.001 < 0.05, then it can be said that the trust (variable X1) and image (X2) together does have influence positively on customer satisfaction (Variable Y) at State Bank (Case Study on Students of Economics IPWIJA Jakarta). While the value of R Square (R2) of 0.676. This shows that at 67.6% confidence (variable X1) and Image (X2) simultaneously does have a positive effect on customer satisfaction (Variable Y) while the remaining 32.4% influenced by other factors.Â Keywords:Trust, Image and Satisfaction